Silicon effects on soil phosphorus availability: results obtained depend on the method used - Uhuegbue, Peter Onyisi; Stein, Mathias; Kalbitz, Karsten; Schaller, Jörg (Frontiers in Environmental Science, 2024)
Phosphorus limitation occurs in many soils as a significant amount of soil P is retained in forms inaccessible to plants, such as bound to iron (Fe) minerals. Prior studies have shown that silicon (Si) can mobilize P from the binding sites of such minerals. Several P extraction methods have been developed to account for different P pools. Nevertheless, each of those methods uses different extractants and mechanisms to extract different P pools in soils. However, there is no study comparing different P extraction methods in the presence of Si fertilization. We tested the effect of Si on P mobility and determined the efficiency of water, calcium-acetate-lactate (CAL), Mehlich-III, and Bray and Kurtz extraction methods for extracting P in the presence of amorphous silica (ASi) fertilization using two soils of contrasting characteristics. Significantly higher amounts of P were found at 3% ASi treatments (10 and 21 mg P kg -1 ) compared to the control (4 and 10 mg P kg -1 ) in the water extract in the high and low-yield soil, respectively just after six hours of extraction and increased with time. This may be explained by Si directly competing with P for sorption to Fe minerals. Using CAL extraction, Si addition showed no effect on P extractability. In contrast, the Mehlich-III and Bray extraction methods showed decreasing P extractability, especially at 3% ASi treatment (95 and 60 mg P kg -1 ) compared to the control (115 and 80 mg P kg -1 ) for the high-yield soil. The decreasing P contents in the presence of Si found in the Mehlich-III and Bray extracts may be attributed to the decrease in extraction effectiveness of the extractants to extract P while extracting Si and Fe. Our results showed that the Mehlich-III and Bray extraction methods may not be suitable for the determination of P availability in the presence of ASi fertilization since both extractants also extract Si and this may limit the completeness of P extraction. Therefore, in the presence of Si fertilizer, the water extraction method may be suitable to determine P availability and mobilization due to ASi.